Impact of sunlight irradiation on CvFAP photodecarboxylation - França, Alexandre S.; Breda, Gabriela C.; De Oliveira, Kleber T.; Almeida, Rodrigo V.; Hollmann, Frank; De Souza, Rodrigo O. M. A. (Frontiers in Catalysis, 2023)
A visible-light-driven photocatalytic decarboxylation of palmitic acid and related fatty acids is described in this study. Remarkable decarboxylation rates have been observed with full conversion in less than 20 min. In this study, we have demonstrated that sunlight irradiation, even on cloudy days, can deliver similar results to traditional LED lamps while using much less energy and minimizing environmental impact. The findings indicate that the process of enzymatic decarboxylation could be useful for the production of different biofuels in the future.